2019
DOI: 10.2991/jegh.k.181231.001
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Hajj Cohorts and Mortality in Saudi Arabia from 2004 to 2011

Abstract: The Hajj is an annual pilgrimage that 1–2 million Muslims undertake in the Kingdom of Saudi Arabia (KSA), which is the largest mass gathering event in the world, as the world’s most populous Muslim nation, Indonesia holds the largest visa quota for the Hajj. All Hajj pilgrims under the quota system are registered in the Indonesian government’s Hajj surveillance database to ensure adherence to the KSA authorities’ health requirements. Performance of the Hajj and its rites are physically demanding, which may pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…The results showing a relationship between having a pre-existing respiratory disease and death in Indonesian pilgrims are in line with other studies (Pane et al, 2019;Rudini, 2016). The available data also indicated that the most common respiratory diseases found in pilgrims were COPD (chronic obstructive pulmonary disease), asthma, and pneumonia.…”
Section: Relationship Between Genetic Risk Factors and Death Caused Bsupporting
confidence: 92%
See 2 more Smart Citations
“…The results showing a relationship between having a pre-existing respiratory disease and death in Indonesian pilgrims are in line with other studies (Pane et al, 2019;Rudini, 2016). The available data also indicated that the most common respiratory diseases found in pilgrims were COPD (chronic obstructive pulmonary disease), asthma, and pneumonia.…”
Section: Relationship Between Genetic Risk Factors and Death Caused Bsupporting
confidence: 92%
“…There are also several risk factors associated with Hajj in Saudi Arabia that can contribute to the severity of respiratory disease, such as a lack of rest and dehydration. Pilgrims with pre-existing respiratory diseases like asthma or COPD may experience asthma attacks or difficulty breathing, which if not dealt with immediately can cause respiratory failure and death (Ihaji, Gerald, Helen, & Ogwuche, 2014;Pane et al, 2019;Rahman, Thu, Arshad, & Van der Putten, 2017;Rudini, 2016).…”
Section: Relationship Between Genetic Risk Factors and Death Caused Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The surveillance system did not collect data from admitted patients in the central hospital for the indicator-based surveillance. This may have resulted in incomplete capture of cases and deaths and the observed low number of deaths compared to other MGs ( Khan et al, 2018 , Pane et al, 2019 ). However, any clustering of events was reported by physicians attending to indoor patients.…”
Section: Discussionmentioning
confidence: 99%
“…This program is due to the in uence of religious spiritual activity in the pattern of disease transmission and plays an essential role in public education in certain religious groups (Charzyńska, 2015;Hall, Meador, & Koenig, 2008). Several research results show that the opinions of ulama are taken into consideration in making decisions in the health sector such as Hajj and Umrah in Islamic religious groups with the spread of disease so that Hajj and Umrah pilgrims in Saudi Arabia are required to have certain vaccines to be allowed to carry out religious activities in that country (Ahmed, Arabi, & Memish, 2006;Memish, Stephens, Steffen, & Ahmed, 2012;Memish et al, 2014;Pane et al, 2019). In addition, a religious approach is also carried out for persuasive methods of behavior change in health problems such as HIV-AIDS (Cotton et al, 2006;Gray, 2004;Noden, Gomes, & Ferreira, 2010;Zou et al, 2009), mental health (Koenig, 2009;Moreira-Almeida, Neto, & Koenig, 2006), and nutrition (Persynaki, Karras, & Pichard, 2017;Trepanowski & Bloomer, 2010).…”
Section: Introductionmentioning
confidence: 99%